The Effectiveness of Four Corners Strategy in Teaching Writing Hortatory Exposition Text - Monitha Geraldine (International Journal of Multi Discipline Science, 2018)
This research investigated the use of Four Corners Strategy in teaching writing hortatory exposition text to the eleventh-grade students of SMAN 10 Pontianak in academic year 2015/2016. Four Corners is a strategy which allows students to think about a concept from four different perspectives of points of view. A quasi-experimental design was implemented to achieve the purpose of this study. The measurement technique was employed in this research. The data collection instrument was written test. This research used the t-test formula to analyze the quantitative data obtained through written test. Furthermore, an analytic scoring rubric was developed to assess the students’ writing in hortatory exposition text. The result of data analysis revealed the superiority of the experimental group to the control group. Hence, the four corners strategy was effective in helping the students to improve their writing hortatory exposition text.